2008
DOI: 10.1097/mat.0b013e318188bde3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Circulatory Support: Current Strategies and Future Directions. Biventricular and Univentricular Mechanical Assistance

Abstract: Mechanical circulatory support is gaining increased recognition as a viable treatment option for pediatric patients who suffer from congenital or acquired heart disease. Historically, the treatment options have been very limited for pediatric patients, but recent technological advances, combined with new research into circulatory support devices, are seeking alternative therapeutics options for infants and children. We present a review of the technological advances of mechanical circulatory support in the pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 59 publications
0
77
0
1
Order By: Relevance
“…3,[33][34][35][36][37] This fundamental change in US clinical practice represents a major milestone for the field of pediatric heart failure therapy. With a growing number of novel miniaturized pediatric VADs now on the horizon, [38][39][40] FDA approval of the EXCOR marks the beginning of a new era in pediatric mechanical circulatory support.…”
Section: Downloaded Frommentioning
confidence: 99%
“…3,[33][34][35][36][37] This fundamental change in US clinical practice represents a major milestone for the field of pediatric heart failure therapy. With a growing number of novel miniaturized pediatric VADs now on the horizon, [38][39][40] FDA approval of the EXCOR marks the beginning of a new era in pediatric mechanical circulatory support.…”
Section: Downloaded Frommentioning
confidence: 99%
“…9 The scalar stress levels within the blood pump were also well below the design criterion of 425 Pa for the development of axial flow assist devices. 27 The linear and increasing trend of the pfHb concentration during the hemolysis experiments met expectations. 3 The design objective for the maximum N.I.H level for an adult left ventricular assist device (LVAD) during a 1-month support duration is 0.01 g/ 100 L. 16 The axial flow pump prototype in this study demonstrated an average N.I.H of 0.0097 g/100 L for all experiments and a maximum N.I.H level of 0.0107 g/100 L. A direct comparison of this design objective to our results for the repeated 6-hr study is not encouraging.…”
Section: Discussionmentioning
confidence: 64%
“…Clinicians have theorized that a mechanical pump specifically designed to augment pressure from the great veins through the lungs would ameliorate the poor physiology of the failing univentricular circulation. 27 Current mechanical blood pumps were designed and developed for adult patients with congestive heart failure and to support the systemic circulation, not the unique anatomic physiology of the cavopulmonary connection. These devices produce pressures far exceeding the desired range to be used for cavopulmonary support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations